Pengaruh Motivasi dan Pelatihan Terhadap Kinerja Karyawan Pada Perguruan Tinggi - Husni Mubarak (Forum Kerjasama Pendidikan Tinggi, 2025)
The purpose of this study was to determine the effect of motivation and training on employee performance at the Sukma Medan School of Management (STIM). The sample was comprised of employees at the Sukma Medan School of Management (STIM). The sample was drawn using probability sampling with a saturated sampling technique, a technique used to determine the sample size when all members of the population are used as samples. The data analysis method used Multiple Linear Regression, hypothesis testing using the coefficient of determination (R2), simultaneous testing (F-test), and partial testing (t-test), while data processing used SPSS. The results showed that the coefficient of determination (R2) test for motivation and training variables explained the variation in employee performance. Furthermore, simultaneously, it showed that motivation and performance variables had a positive and significant effect on employee performance. Partially, motivation had no effect on employee performance, and partially, training variables had an effect on employee performance.